Robust Temperature Control of Chemical Batch Reactor using Sliding Mode Control (International Journal of Scientific Research and Management (IJSRM), 2017)
In this paper a nonlinear model of chemical batch reactor is considered. In this two chemicals with specified concentrations are mixed and they are maintained at desired temperature. The tracking problem is considered. The modified sliding mode control is applied for the controller design and robust tracking of the desired temperature trajectory is achieved. Therefore objective of robust tracking with disturbance rejection with finite time convergence is achieved. The stability of the sliding surface is analysed with the lyapunov method. The results are compared with the classical sliding mode control and analysed.